Microbiological status of root canal after unsuccessful endodontic treatment - Nešković Jelena; Jovanović-Medojević Milica; Grga Đurica; Popović Branka; Živković Slavoljub (Serbian Medical Society - Dental Section, Belgrade, 2018)
Introduction the main objective of endodontic treatment is to eliminate infection from root canal and prevent re-infection by three-dimensional hermetic obturation of the canal system. Endodontic failure can occur due to inability of complete control and elimination of infection from the root canal. The aim of this study is to investigate, by PCR technique, microbiological status of previously endodontically unsuccessfully treated teeth immediately after the removal of obturation material. Material and Methods the analysis included 30 teeth indicated for endodontic retreatment. After removing previous root canal filling material, the bacteriological sample was taken by sterile instrument (# 15) and paper points. Standard PCR technique was used to analyze the incidence of E.faecalis, P.micros, P.intermedia, P. endodontalis and a.actinomycetemcomitans. Results Positive bacteriological findings were registered in 80% of cases, while bacteria were not identified in 20% of all samples (all taken from the root canals without significant changes in periapical tissue). From 24 canals with identified bacteria, 17 had affected apical periodontium. The most dominant microbe in root canals with positive bacteriological finding was E.faecalis (83.3% of the canals) and P.intermedia (75%). In case of teeth with chronic periapical changes, the most common was E. faecalis (94%) and P.intermedia (82.3%). Conclusion the presence of periapical lesions significantly affects microbiological status of endodontically treated teeth. The presence of bacteria was confirmed in most teeth with periapical lesions, while the most frequently identified bacteria were E. faecalis, P.intermedia and P.micros.